2016
DOI: 10.1007/s00421-016-3474-z
|View full text |Cite
|
Sign up to set email alerts
|

Running decreases knee intra-articular cytokine and cartilage oligomeric matrix concentrations: a pilot study

Abstract: Running appears to decrease knee intra-articular pro-inflammatory cytokine concentration and facilitates the movement of COMP from the joint space to the serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 38 publications
0
37
2
2
Order By: Relevance
“…They found no differences between groups in acute serum COMP concentrations in response to exercise or over time, after the aerobic and RE sessions . In contrast, Hyldahl et al . found an increase in COMP concentration in six healthy individuals after 30 min of running and also provided additional information suggesting that serum COMP following lower body exercise may largely be from the knee joint, since they found a significant inverse relation between synovial fluid and serum COMP concentrations after the exercise session .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…They found no differences between groups in acute serum COMP concentrations in response to exercise or over time, after the aerobic and RE sessions . In contrast, Hyldahl et al . found an increase in COMP concentration in six healthy individuals after 30 min of running and also provided additional information suggesting that serum COMP following lower body exercise may largely be from the knee joint, since they found a significant inverse relation between synovial fluid and serum COMP concentrations after the exercise session .…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, Hyldahl et al . found an increase in COMP concentration in six healthy individuals after 30 min of running and also provided additional information suggesting that serum COMP following lower body exercise may largely be from the knee joint, since they found a significant inverse relation between synovial fluid and serum COMP concentrations after the exercise session . In a study involving 45 male runners, Mündermann et al .…”
Section: Discussionmentioning
confidence: 96%
“…These results indicate that participants followed the instructions on maintaining consistent daily routines, and hence boundary conditions were comparable between test days (time of day, food intake, previous physical activity level, etc.). Comparisons of baseline concentrations to those reported in other studies are difficult because different assays were used 19,20,33 or results were reported in other units (e.g., units/liter 25e27,36 ) that cannot be converted because some assays target different components or fragments of COMP. Baseline sCOMP levels in our study were similar in men and in women.…”
Section: Discussionmentioning
confidence: 99%
“…The net flow across the synovial interstitium can be enhanced during joint flexion due to an increased intra‐articular fluid pressure . Beyond that, Hyldahl et al showed that the decrease of COMP in synovial fluid measured in recreational runners 15 min after a running intervention correlated with the increase of serum COMP observed immediately after running and thus give first indications that elevated serum COMP levels after physical activity are in part the result of a better transport of COMP from the synovial fluid into the lymphatic system and bloodstream. Other possible sources of COMP should be also kept in mind.…”
Section: Discussionmentioning
confidence: 99%